2004
DOI: 10.1016/s1094-2025(03)00052-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying embodied technological change

Abstract: Bureau for very useful comments. Plutarchos Sakellaris would like to thank the staff of the Industrial Output Section of the Federal Reserve Board for their hospitality while he was working on this paper. Daniel Wilson would like to thank Clopper Almon and the staff of Inforum for their generous support, financial and otherwise, of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 35 publications
4
39
1
1
Order By: Relevance
“…29 It is also well-known that the speed of convergence in a growth model generally tends to slow down as the desire for consumption smoothing, θ, rises and the population growth rate falls, respectively. 30 As expected, this holds in the present framework as well. At the same time, as documented in Appendix G, the qualitative patterns displayed by the graphs above go through for alternative values of θ and n, respectively.…”
Section: Other Aspectssupporting
confidence: 87%
See 2 more Smart Citations
“…29 It is also well-known that the speed of convergence in a growth model generally tends to slow down as the desire for consumption smoothing, θ, rises and the population growth rate falls, respectively. 30 As expected, this holds in the present framework as well. At the same time, as documented in Appendix G, the qualitative patterns displayed by the graphs above go through for alternative values of θ and n, respectively.…”
Section: Other Aspectssupporting
confidence: 87%
“…Combining Lemma D1 and D2 we have that when (A1) and (A2) hold together with λ > 0 or (β > 0 and θ ̸ = α), then generically C 2i = c 2 v 2 i ̸ = 0, i = 1, 2, 3. In the light of (30) it follows that in this case the same asymptotic speed of convergence, −η 2 , applies to all three variables in the dynamic system. That this will also be the asymptotic speed of convergence of y t /y * t follows by (31).…”
Section: Local Existence and Uniqueness Of A Convergent Solutionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies have shown that quality upgrading in advanced economies may have the effect of leaving less developed countries out of international markets (e.g. Murphy and Shleifer, 1997;Fan, 2004 (Greenwood et al,1997;Cummins and Violante, 2002;Sakellaris and Wilson, 2004). In light of these findings, the transmission of sustained growth through the terms of trade seems more than just a theoretical possibility.…”
Section: Introductionmentioning
confidence: 95%
“…This gain is not sizeable without investment and without trade liberalisation in capital goods, as the production of capital equipment is concentrated in a very limited number of R&D intensive countries. According to Sakellaris and Wilson (2004), embodied technological change could account for as much as two-thirds of TFP growth in US manufacturing plants.…”
mentioning
confidence: 99%